(untitled) (Jurnal Teknologi (Sciences & Engineering), 2012)
Knoevenagel condensation reaction (KCR) and Pechmann condensation reaction are the simplest and most widely used method to synthesize various substituted coumarins. The compounds such as 3–acetylcoumarin, 3–acetyl–7–(diethylamino)coumarin, and 7–(diethylamino)–3–(1–oxobutyl)coumarin were synthesized by KCR method which involved the condensation of salicylaldehyde or 4–(diethylamino)salicylaldehyde with ethyl acetoacetate, 4–(diethylamino)– salicylaldehyde with ethyl butyrylacetate in the presence of dimethylamine as a catalyst. Meanwhile, 7–hydroxy–4–methylcoumarin, 4–methyl–2H–benzo[h]chromen–2–one, 7–hydroxy–4,8–dimethyl– coumarin, 7–hydroxy–4–propylcoumarin, 4–propyl–2H–benzo[h]chromen–2–one, 7–hydroxy–8–methyl–4–propylcoumarin and 7,8–dihydroxy–4–propylcoumarin were synthesized through Pechmann condensation reaction by condensation of resorcinol, 1–napthol or 2–methylresorcinol with ethyl acetoacetate, and resorcinol, 1–napthol, 2–methylresorcinol or pyrogallol with ethyl butyrylacetate, respectively in the presence of sulphuric acid as a catalyst. All compounds were characterized by spectroscopic techniques using infrared (IR), proton and carbon nuclear magnetic resonance (1H and 13C NMR).